Efficacy and safety comparison between liraglutide as add-on therapy to insulin and insulin dose-increase in Chinese subjects with poorly controlled type 2 diabetes and abdominal obesity - Li, Chun-jun (BioMed Central, 2012)
OBJECTIVE: To assess the efficacy and safety of adding liraglutide to established insulin therapy in poorly controlled Chinese subjects with type 2 diabetes and abdominal obesity compared with increasing insulin dose. METHODS: A 12-week, randomized, parallel-group study was carried out. A total of 84 patients completed the trial who had been randomly assigned to either the liraglutide-added group or the insulin-increasing group while continuing current insulin based treatment. Insulin dose was reduced by 0-30% upon the initiation of liraglutide. Insulin doses were subsequently adjusted to optimized glycemic control. Glycosylated hemoglobin (HbA(1c)) values, blood glucose, total daily insulin dose, body weight, waist circumference, and the number of hypoglycemic events and adverse events were evaluated. RESULTS: At the end of study, the mean reduction in HbA(1c) between the liraglutide-added group and the insulin-increasing group was not significantly different (1.9% vs. 1.77%, p>0.05). However, the percentage of subjects reaching the composite endpoint of HbA1c ≤ 7.0% with no weight gain and no hypoglycemia, was significantly higher in the liraglutide-added group than in the insulin-increasing group (67% vs. 19%, p<0.001). Add-on liraglutide treatment significantly reduced mean body weight (5.62 kg, p<0.01), waist circumference (5.70 cm, p<0.01), body mass index (BMI) (1.93 kg/m(2), p<0.01) and daily total insulin dose (dropped by 66%) during 12-week treatment period, while all of these significantly increased with insulin increasing treatment. Add-on liraglutide treated patients had lower rate of hypoglycemic events and greater insulin and oral antidiabetic drugs discontinuation. Gastrointestinal disorders were the most common adverse events in the liraglutide added treatment, but were transient. CONCLUSIONS: Addition of liraglutide to abdominally obese, insulin-treated patients led to improvement in glycemic control similar to that achieved by increasing insulin dosage, but with a lower daily dose of insulin and fewer hypoglycemic events. Adding liraglutide to insulin also induced a significant reduction in body weight and waist circumference. Liraglutide combined with insulin may be the best treatment option for poorly controlled type 2 diabetes and abdominal obesity.